UJI INFEKSI Cylindrocladium sp., TERHADAP KLON HIBRIDA TURUNAN Eucalyptus grandis x Eucalyptus urophylla - Berlianta R. Siallagan; Nelly Anna; Edy Batara Mulya Siregar (Program studi Kehutanan USU, 2015)
Cylindrocladium sp. is one of the diseases caused on leaf. Eucalyptus sp. is a plant that is used in the pulp industry. The objective of this study to characterize the symptoms of foliar diseases and measure the desiases severity and diseases incidence on clone IND 65, IND 68 and IND 69. The infection of Cylindrocladium sp. was implemented with spraying method. Cylindrocladium sp., showed the symptoms was redness brown spots and patches of grayish. Based on the diseases severity criteria three clones classifield as resistant clones. Based on the diseases incidence criteria of IND 65, IND 68 were classified as resistant and IND 69 quite a bit resistant.Key words: Cylindrocladium sp., Eucalyptus sp., Infection test.